2018
DOI: 10.1093/mnras/sty3128
|View full text |Cite
|
Sign up to set email alerts
|

The environments of luminous radio-WISE selected infrared galaxies

Abstract: We have observed the environments of a population of 33 heavily dust obscured, ultraluminous, high-redshift galaxies, selected using WISE and NVSS at z >1.3 with the Infra-Red Array Camera on the Spitzer Space Telescope over 5.12 ×5.12 fields. Colour selections are used to quantify any potential overdensities of companion galaxies in these fields. We find no significant excess of galaxies with the standard colour selection for IRAC colours of [3.6] − [4.5] > −0.1 consistent with galaxies at z >1.3 across the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
3
8
0
Order By: Relevance
“…The sources also have high bolometric luminosity similar to those of ULIRGs and HyperLIRGs (L IR > 10 12−13 L ). They are typically found in overdense environments, suggesting some of our sources are likely to be tracers of unvirialized protocluster regions (Silva et al 2015;Jones et al 2015;Penney et al 2019), consistent with both observations (e.g., Miley & De Breuck 2008;Dannerbauer et al 2014) and simulations (e.g., Chiang et al 2017) of z > 2 radio-loud quasars. The black hole masses have been estimated from MIR-submillimeter SED modeling to be in the range log(M BH /M ) = 7.7 − 10.2 (Paper I), and from [OIII] line luminosities as a proxy for bolometric luminosity to be in the range log(M BH /M ) = 7.9 − 9.4 (Kim et al 2013;Ferris et al 2021).…”
Section: Introductionsupporting
confidence: 85%
“…The sources also have high bolometric luminosity similar to those of ULIRGs and HyperLIRGs (L IR > 10 12−13 L ). They are typically found in overdense environments, suggesting some of our sources are likely to be tracers of unvirialized protocluster regions (Silva et al 2015;Jones et al 2015;Penney et al 2019), consistent with both observations (e.g., Miley & De Breuck 2008;Dannerbauer et al 2014) and simulations (e.g., Chiang et al 2017) of z > 2 radio-loud quasars. The black hole masses have been estimated from MIR-submillimeter SED modeling to be in the range log(M BH /M ) = 7.7 − 10.2 (Paper I), and from [OIII] line luminosities as a proxy for bolometric luminosity to be in the range log(M BH /M ) = 7.9 − 9.4 (Kim et al 2013;Ferris et al 2021).…”
Section: Introductionsupporting
confidence: 85%
“…We find two Hot DOGs with detections in Jones et al (2014), which have similar q IR values to W2305-0039, suggesting a possible subclass of radio-loud Hot DOGs. It should be noted that these Hot DOGs have different selection criteria than the radio-WISE selected galaxies in Lonsdale et al (2015), as shown by the selection comparison in Penney et al (2019). There are Hot DOGs in both works without detections in FIRST, with lower limits for the q-values that agree with the median values for Ivison et al (2010) and Thomson et al (2014), suggesting that these galaxies could agree with the FIRradio correlation.…”
Section: Fir-radio Correlationmentioning
confidence: 86%
“…With well established radio galaxies apparently found in proto-clusters (Wylezalek et al 2013;Hatch et al 2014), and the environments of RWGs showing a 4-6 times overdensity of ultraluminous, dusty, high-redshift 850 -𝜇m -selected galaxies on the sky (SMGs, e.g. Blain et al 2002;Casey et al 2014) as compared with typical blank fields (Jones et al 2015;Silva et al 2015), and a more modest overdensity of red Spitzer-IRAC-selected galaxies (Penney et al 2019). This is potentially consistent with RWGs, and these ultra-luminous, dusty AGNs in general, being found in an active, extended still-virializing filamentary proto-cluster environments over scales in excess of five arcmin (3 Mpc) consistent with theoretical models (e.g.…”
Section: Introductionmentioning
confidence: 91%